2004
DOI: 10.1111/j.1420-9101.2004.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis affecting litter size in mice

Abstract: Litter size is an important reproductive trait as it makes a major contribution to fitness. Generally, traits closely related to fitness show low heritability perhaps because of the corrosive effects of directional natural selection on the additive genetic variance. Nonetheless, low heritability does not imply, necessarily, a complete absence of genetic variation because genetic interactions (epistasis and dominance) contribute to variation in traits displaying strong heterosis in crosses, such as litter size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 44 publications
5
66
2
Order By: Relevance
“…These results suggested that it was relatively easy to find strong epistasis (for example, h epi 2 47.5%), but difficult to detect weak ones given the population size. Our observations are roughly in line with earlier studies: four interaction-only pairs detected from an F 2 mouse population (size is 510, 166 females) explained about 36% of the total variation in litter size (that is h epi 2 ¼ 9% on average) (Peripato et al, 2004); most epistatic pairs detected for obesity-related traits using 513 F 2 mice had a h epi 2 42% despite the relatively relaxed thresholds that were used (Stylianou et al, 2006). Increasing the population size is a good option to increase power (Carlborg et al, 2003;Ma et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…These results suggested that it was relatively easy to find strong epistasis (for example, h epi 2 47.5%), but difficult to detect weak ones given the population size. Our observations are roughly in line with earlier studies: four interaction-only pairs detected from an F 2 mouse population (size is 510, 166 females) explained about 36% of the total variation in litter size (that is h epi 2 ¼ 9% on average) (Peripato et al, 2004); most epistatic pairs detected for obesity-related traits using 513 F 2 mice had a h epi 2 42% despite the relatively relaxed thresholds that were used (Stylianou et al, 2006). Increasing the population size is a good option to increase power (Carlborg et al, 2003;Ma et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Selection experiments for increased litter size have been performed in various strains of mice and heritability of litter size is estimated to be relatively low at 15% (Beniwal et al, 1992;Gutiérrez et al, 2006;Peripato et al, 2004). In the present study we showed a slight positive relationship (with a slope of 0.16) between litter size of mothers and their biological daughters, but this relationship did not reach significance.…”
Section: Discussionmentioning
confidence: 34%
“…In fact, by not studying interactions in an F2 cross there is a risk that susceptibility loci might be missed. 20,21 In addition, careful statistical analysis is important. We chose to use the R/qtl software 22 to analyze genetic interactions.…”
Section: Discussionmentioning
confidence: 99%